Mengapa Fesyen Muslim Indonesia Tertinggal di Pasar Global? Analisis Mikroekonomi Islam atas Desain, Branding Halal, dan Distribusi - Mardiah, Ainul; Kalputri, Inten; Ramadhani, Wahyu; Hadi Insani, Ikhwan; Elvira, Rini (Imara: Jurnal Riset Ekonomi Islam, 2025)
Background. The global Muslim fashion industry has expanded rapidly, driven by increasing demand for halal and ethical products. Yet Indonesia despite being the world’s largest Muslim-majority country has not translated its demographic and industrial potential into strong global competitiveness, indicating persistent structural constraints in the national Muslim fashion ecosystem. Purpose. This qualitative study aimed to examine the key factors constraining the global competitiveness of Indonesian Muslim fashion from an Islamic microeconomic perspective, with particular emphasis on how Sharia-based economic values are (not) integrated across the industry value chain. Method. Employing a qualitative case study design, the study draws on a systematic review of academic literature, global industry reports, and policy and trade documents related to the halal industry and Muslim fashion. The collected materials were analysed through document analysis to identify recurring policy, market, and value-chain patterns relevant to Islamic microeconomic principles. Results. The findings show that Indonesia’s limited competitiveness is associated with (1) fragmented policy frameworks that treat halal primarily as administrative compliance rather than a competitiveness fashion sector